Advances in Porous Silicon–Based Nanomaterials for Diagnostic and Therapeutic Applications. Issue 1 (10th October 2018) - Tieu, Terence; Alba, Maria; Elnathan, Roey; Cifuentes‐Rius, Anna; Voelcker, Nicolas H.
Abstract: This review provides a perspective on porous silicon (pSi)–based nanomaterials including nanoparticles, nanowires, and thin films, that are currently being used in advanced therapy, imaging, and sensing, with a focus on their effective use in future clinical settings. The achievement of both controlled geometry and architecture, and surface chemistry motifs, are presented as the two key parameters that dictate the nature of interactions with the biological entities. The authors discuss the role of the degradation kinetics in a biological environment into nontoxic by‐products. pSi is presented as increasingly fulfilling a central task in various biomedical applications and clinical settings, owing to its unique physiochemical properties. Abstract : Porous silicon (pSi) is a unique biomaterial that has gained significant traction recently for biomedical applications . pSi exhibits attractive properties including its tunable geometry, high specific surface area, and versatile surface chemistry. The use of pSi structures in both drug delivery and biosensing is reviewed and discussed.